PA12 nylon dust reduction of selective laser sintering reprocessing by optimization of refresh rate and powder handling - Ali Detho, Amir (2021)
In this work, a novel composite adsorbent from coconut activated shell carbon (CAC), green mussel shell (GMS) and natural zeolite (ZEO) binding with ordinary Portland cement (OPC) were investigated over a range of two problematic parameters as known as ammoniacal nitrogen (NH3-N) and COD. The optimum conditions for adsorption in the batch study occurred at pH 7, shaking speed of 200 rpm, contact time of 120 min, adsorbent dosage of 5g and particle size of 2.36–3.35 mm. The adsorption isotherm behavior was investigated using Langmuir and Freundlich model, while adsorption kinetic behavior was investigated using Pseudo-first- and second-order model. The column adsorption experiment were conducted to investigate the varying effect of flowrate of (1.5, 2.0, 2.5 and 3.0 mL/min). The kinetics of adsorption were studied using Thomas, Adam Bohart and Yoon-Nelson model. The composite adsorbents were further tested for regeneration over five adsorption-desorption generation cycles. Based on the finding results, the best optimum ratio towards NH3-N and COD removal from leachate was achieved i-e, CAC 2.5g, GMS 1.5g and ZEO 1g respectively. The determination of isotherm adsorption describe the experimental result found better suited to the Langmuir isotherm. This composite adsorbents mainly shows monolayer adsorption coverage was predominant. Conversely, the kinetic adsorption obeyed well the second-order kinetic model that describe sorption process rate were controlling by the second-order kinetic model mechanism (chemisorption). Column adsorption result describes that the percentage removal of NH3-N and COD was achieved up to 99.78% at lower flowrate 1.5 mL/min which indicates in longer break-through and exhaustion times. Meanwhile, the adsorption experiment data fitted well-established with column adsorption model, namely, Thomas, Adam Bohart and Yoon-Nelson model. The finding results revealed that Thomas and Yoon-Nelson model found better suited as compared with Adam Bohart model. In conclusion, this research has successfully proven that the composite adsorbent is a suitable adsorbent for removal percentage of NH3-N and COD from landfill leachate.